Analysis of Agricultural Land Classification in East Kotawaringin District, Central Kalimantan Province using Landsat 8-OLI Image - Maria ULFA; Novitasari Sudar RIYANTI; M. Holilur ROHMAN; Emy KHILMIAH; Jihan Ratna FAUZIAH; Ahmad Ardinata PRIANDANA; Sabrina Auliauz ZAHROH; Fahmi Arif KURNIANTO (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose:This research aims to map agricultural land in East Kotawaringin Regency, Kalimantan Province, and analyze it using Landsat 8 OLI satellite imagery in 2023.Methodology:The method used in this research is supervised classification, which will then carry out a data analysis process related to natural conditions in the field. Based on the results of satellite image data processing, there are five categories of land cover classification in the East Kotawaringin Regency area: built-up land, empty land, fields/moors, gardens and forests.Findings:According to the accuracy test results, the overall accuracy value of satellite imagery in East Kotawaringin Regency is 87%. Community activities, such as economic activities and meeting needs for public facilities and housing, influence the distribution of existing land cover areas.Implication:The classification results obtained later through maps of agricultural land in East Kotawaringin Regency can be used to find various studies, especially on expanding the agricultural sector.